The Power and Promise of Developmental Systems Theory - Meynell, Letitia (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2008)
I argue that it is time for many feminists to rethink their attitudes towards evolutionary biology, not because feminists have been wrong to be deeply sceptical about many of its claims, both explicit and implicit, but because biology itself has changed. A new appreciation for the importance of development in biology has become mainstream and a new ontology, associated with developmental systems theory (DST), has been introduced over the last two decades. This turn challenges some of the features of evolutionary biology that have most troubled feminists. DST undermines the idea of biological essences and challenges both nature/nurture and nature/culture distinctions. Freed from these conceptual constraints, evolutionary biology no longer poses the problems that have justified feminist scepticism. Indeed, feminists have already found useful applications for DST and I argue that they should expand their use of DST to support more radical and wide-ranging political theories.